2009
DOI: 10.1186/ar2698
|View full text |Cite
|
Sign up to set email alerts
|

Replication of recently identified systemic lupus erythematosus genetic associations: a case–control study

Abstract: Introduction We aimed to replicate association of newly identified systemic lupus erythematosus (SLE) loci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
107
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(115 citation statements)
references
References 27 publications
7
107
1
Order By: Relevance
“…Many SNPs are in the coding region, and .100 nonsynonymous variants have been annotated. Genome-wide association studies and more targeted candidate approaches have shown strong linkage of Tyk2 haplotypes or individual SNPs to systemic and organ-specific autoimmune diseases, namely systemic lupus erythematosus (SLE) (11)(12)(13)(14), multiple sclerosis (MS) (15)(16)(17)(18)(19), Crohn's disease (20)(21)(22), psoriasis (23), type 1 diabetes (24), endometriosis-related infertility (25), and primary biliary cirrhosis (26) (Table I). Interestingly, one rare MSassociated variant (rs34536443) is considered to be protective, whereas another (rs55762744) was recently identified as a risk allele (17).…”
mentioning
confidence: 99%
“…Many SNPs are in the coding region, and .100 nonsynonymous variants have been annotated. Genome-wide association studies and more targeted candidate approaches have shown strong linkage of Tyk2 haplotypes or individual SNPs to systemic and organ-specific autoimmune diseases, namely systemic lupus erythematosus (SLE) (11)(12)(13)(14), multiple sclerosis (MS) (15)(16)(17)(18)(19), Crohn's disease (20)(21)(22), psoriasis (23), type 1 diabetes (24), endometriosis-related infertility (25), and primary biliary cirrhosis (26) (Table I). Interestingly, one rare MSassociated variant (rs34536443) is considered to be protective, whereas another (rs55762744) was recently identified as a risk allele (17).…”
mentioning
confidence: 99%
“…9 Interestingly, another functional SNP in TYK2 was recently confirmed to confer susceptibility to systemic lupus erythematosus (SLE). 15 Comparing the MS-and SLE-associated TYK2 SNPs, that is, rs34536443 with rs2304256 in Haploview v.4Á1 (using the CEU individuals from the HapMap project phase 1, 2 and 3 (http://www. hapmap.org/ and http://www.ncbi.nlm.nih.gov/)), there was no evidence of linkage disequilibrium (LD) between these SNPs (r 2 ¼0.044).…”
Section: Discussionmentioning
confidence: 99%
“…PXK domain containing serine/threonine kinase and act as modulator of Na, K-ATPase enzymatic and ion pump activities (Mao, 2005). It was identified as a novel candidate gene for systemic lupus erythematosus (SLE) from genomewide association studies (GWAS) in Caucasians (Suarez-Gestal, 2009). The association of PXK rs6445975 with SLE observed in Caucasians was not replication study in Hong Kong Chinese and Koreans (Kim, 2011;.…”
Section: Chromosome 3 41 Phox Homology (Px) Domain Kinase (Pxk) (3pmentioning
confidence: 99%